Comparative Title Knowledge, Attitude, And Perception About Respiratory Diseases Associated With Biomass Smoke Exposure Among Rural Women In West Bengal - Mondal, Subhra; Kshatriya, Ravish; Ghanta, Jyotirmoy (Journal of Neonatal Surgery, 2025)
Background: Biomass smoke is a primary source of indoor air pollution in many rural settings, contributing to an increased burden of respiratory symptoms and diseases. In West Bengal, India, women face disproportionate exposure due to traditional cooking practices using biomass fuels like wood, crop residue, and dung. Understanding their knowledge, attitude, and perception (KAP) of these health risks is crucial for designing targeted interventions. Methods: This cross-sectional study was conducted among 400 rural women in a single selected district of West Bengal from April to October 2023. A multistage cluster sampling strategy was used to ensure representation of various administrative blocks and villages within the district. Structured interviews assessed socio-demographics, fuel use, ventilation, and KAP regarding respiratory diseases. Knowledge scores were derived from participants’ understanding of common respiratory conditions (e.g., chronic cough, breathlessness). Descriptive statistics, chi-square tests, and logistic regression were performed using SPSS version 25. Results: Approximately 38% of respondents showed adequate knowledge of the respiratory risks linked to biomass smoke, with 32% recognizing persistent cough and difficulty in breathing as common health effects. Although 55% believed that improved cookstoves or cleaner fuels could prevent respiratory problems, only 28% consistently used cleaner alternatives. The main barriers were financial limitations, inconsistent fuel supply, and low awareness. Secondary or higher education and exposure to health awareness programs were significantly associated with better KAP (p < 0.05). Conclusion: This study highlights suboptimal KAP concerning biomass smoke–related respiratory diseases among rural women in a selected district of West Bengal. Enhancing educational outreach, improving cookstove availability, and ensuring affordable, cleaner fuels are recommended to reduce the respiratory health burden. A multifaceted intervention addressing socio-economic and cultural determinants is crucial for effective policy implementation.